Uso de las nuevas tecnologías de la información por parte de las secretarias de las empresas públicas y privadas del sector urbano del cantón Salcedo - Caisalitin Velasque, Lilia Alexandra (2015)
This research is about "use of new information and communications technology for secretaries", the same as was done by research and with the participation of managers and secretaries of public and private sector companies Urban Salcedo canton, through the methodology used could determine the lack of knowledge and use of TIC´S by the secretaries in the workplace, revealing the difficulties presented by the lack of training and updating. Having performed the analysis and interpretation of results obtained during the implementation of surveys and interviews to managers and secretaries of public and private companies, it was decided that it is necessary and indispensable to have a broad knowledge about the use of TIC´S, the same that will improve development and business growth in a competitive world….